Ostseeraum, Deutschland/Polen: Die frühmittelalterlichen Emporien im südwestlichen Ostseeraum und ihre Häfen - Messal, Sebastian; Jörns, Hauke; Karle, Martina; Lüth, Friedrich (e-Forschungsberichte des DAI, 2023)
During the Early Middle Ages the Baltic Sea region formed the zone of contact between the Scandinavian kingdoms, the Frankish Empire, and the Baltic and Slavic tribal areas. In the area between the Bay of Wismar and Gdańsk Bay, populated by Slavs during the Early and High Middle Ages, nine maritime trading centres have been identified so far; their harbours were key interfaces between land and water transport. The research plan envisages a systematic and interdisciplinary investigation of the harbour structures of these early medieval sites from a topographical, economic and social perspective.